Preparation, characterization and protein sorption of photo-crosslinked cell membrane-mimicking chitosan-based hydrogels. (20th October 2016) - Zhao, Yunfei; Ma, Liubo; Zeng, Rong; Tu, Mei; Zhao, Jianhao
Highlights: Photocrosslinkable biomimetic chitosan derivative PCCs-GMA was synthesized. Biomimetic PCCs-GMA hydrogels showed tunable mechanical and swelling properties. PCCs-GMA hydrogels showed better blood compatibility than Cs-GMA hydrogels. PCCs-GMA hydrogels showed low protein adsorption comparable with PEG-DA hydrogels. Abstract: Photocrosslinkable biomimetic chitosan derivative, glycidyl methacrylate-phosphorylcholine-chitosan (PCCs-GMA) was synthesized through the combination of Atherton-Todd reaction for coupling phosphorylcholine and ring opening reaction of epoxides for attaching GMA, and confirmed by 1 H and 31 P NMR and Fourier transform infrared (FTIR) spectroscopy. The photo-crosslinking reaction of PCCs-GMA with different degree of substitution (DS) of GMA allowed the formation of biomimetic hydrogels with tunable mechanical and swelling properties. Cold crystallization behaviors ascribed to their restrained freezing bound water were investigated using differential scanning calorimetry (DSC). The rheological and swelling behaviors, hemolysis as well as protein sorption of PCCs-GMA hydrogels were investigated in terms of the DS of GMA, using fibrinogen, bovine serum albumin and lysozyme as model proteins. Low irreversible protein sorption and non hemolytic results indicated that photo-crosslinked PCCs-GMA hydrogels may offer a promising candidate material with resistance to protein fouling in biomedical applications.